2008
DOI: 10.3181/0801-rm-33
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Glucose Uptake and Suppressed Expression/Translocation of Myocardium Glucose Transport-4 in Dogs Undergoing Ischemia-Reperfusion

Abstract: Impaired glucose metabolism is implicated in cardiac failure during ischemia-reperfusion. This study examined cardiac glucose uptake and expression of glucose transport-4 (GLUT-4) in dogs undergoing ischemia-reperfusion. Cardiac ischemia was induced by cardiopulmonary bypass for 30 min or 120 min in dogs. Plasma insulin and glucose concentrations were measured at pre-bypass (control), and aortic cross-clamp off (ischemia-reperfusion) at 15, 45, and 75 min. At the same time, the left ventricle biopsies were tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
(65 reference statements)
3
15
0
2
Order By: Relevance
“…Upon I/R injury, major enzymes involved in energy metabolism, methyl metabolism, lipid synthesis, and amino acid metabolism were downregulated, indicating a global impairment of metabolic activity in liver tissues, which might reflect an adaptive mechanism for the hepatocyte to reduce energy dissipation under a condition of ischemia and hypoxia. This observation is partially in accordance with a recent observation in ischemic heart that cardiac I/R injury are associated with reduced myocardium glucose uptake, utilization, and glycogen content [28]. It is worth mention that pretreated the mice with 10 min of ischemia and 10 min of reperfusion before I/R partly reversed the suppression of hepatic metabolic activity, suggesting a possible mechanism of the hepatoprotective effect of IPC.…”
Section: Discussionsupporting
confidence: 91%
“…Upon I/R injury, major enzymes involved in energy metabolism, methyl metabolism, lipid synthesis, and amino acid metabolism were downregulated, indicating a global impairment of metabolic activity in liver tissues, which might reflect an adaptive mechanism for the hepatocyte to reduce energy dissipation under a condition of ischemia and hypoxia. This observation is partially in accordance with a recent observation in ischemic heart that cardiac I/R injury are associated with reduced myocardium glucose uptake, utilization, and glycogen content [28]. It is worth mention that pretreated the mice with 10 min of ischemia and 10 min of reperfusion before I/R partly reversed the suppression of hepatic metabolic activity, suggesting a possible mechanism of the hepatoprotective effect of IPC.…”
Section: Discussionsupporting
confidence: 91%
“…The current study showed that the expression of cytoplasmic aconitate hydratase was down-regulated by I/R, indicating a global impairment of metabolic activity and reduced energy dissipation in intestinal mucosa tissue. This observation was partially in accordance with a recent observation in ischemic heart, which showed that cardiac I/R injury was associated with reduced myocardium glucose uptake, utilization, and glycogen content [16]. It is worthy to mention that post-treatment of the rat with three cycles of reperfusion of SMA for 30 s followed by occlusion for 30 s between ischemia and reperfusion up-regulated the expression of cytoplasmic aconitate hydratase, which might be a potential mechanism whereby IPo conferred intestinal protection.…”
Section: Discussionsupporting
confidence: 93%
“…The current findings may also have physiologic relevance to other situations such as the ischemic heart, which loses its normal substrate flexibility and becomes more dependent upon glucose as a metabolic fuel [28]. Finally, the ultimate question is whether the survival benefit of exenatide in a murine model will translate to human patients.…”
Section: Discussionmentioning
confidence: 87%